ID 70 – Cortical inhibition and excitation by bilateral transcranial alternating current stimulation. Issue 3 (March 2016) - Cancelli, A.; Cottone, C.; Zito, G.; Di Giorgio, M.; Pasqualetti, P.; Tecchio, F.
Abstract : Purpose: Transcranial electric stimulations (tES) with amplitude-modulated currents are promising tools to enhance neuromodulation effects. It is essential to select the correct cortical targets and inhibitory/excitatory protocols to reverse changes in specific networks. We aimed at assessing the dependence of cortical excitability changes on the current amplitude of 20 Hz transcranial alternating current stimulation (tACS) over the bilateral primary motor cortex. Methods: We chose two amplitude ranges of the stimulations, around 25 μ A/cm2 and 63 μ A/cm2 from peak to peak, with three values (at steps of about 2.5%) around each, to generate, respectively, inhibitory and excitatory effects of the primary motor cortex. We checked such changes online through transcranial magnetic stimulation (TMS)-induced motor evoked potentials (MEPs). Results: Cortical excitability changes depended upon current density (p=.001). Low current densities decreased MEP amplitudes (inhibition) while high current densities increased them (excitation). Conclusions: tACS targeting bilateral homologous cortical areas can induce online inhibition or excitation as a function of the current density.